One-dimensional confinement of a nanosized metal organic framework in carbon nanofibers for improved gas adsorption - Pachfule, Pradip; Balan, Beena K.; Kurungot, Sreekumar; Banerjee, Rahul (Chemical Communications, 2012)
The loading of a Zn-terephthalate based MOF in the inner cavity as well as on the outer walls of a hollow carbon nanofiber (CNF) creates MOF@CNF hybrids. This hybrid ``MOF@CNF'' displayed improved thermal stability as well as gas adsorption compared to the individual counterparts.

One-dimensional water cages with repeat units of (H2O)(24) resembling pagodane trapped in a 3D coordination polymer: proton conduction and tunable luminescence emission by adsorption of anionic dyes - Maity, Kartik; Kundu, Tanay; Banerjee, Rahul; Biradha, Kumar (Crystengcomm, 2015)
A 3D-coordination polymer was shown to trap one-dimensional polyhedral water cages consisting of repeat units of (H2O)(24), the geometry of which resembles the exotic organic molecule pagodane. Further, this material exhibited proton conduction ability and tunable luminescence emission by adsorption of anionic dyes such as the fluorescein dianion.